Utility of High-Resolution Ultrasonography in the Evaluation of Posterior Segment Ocular Lesions Using Sensitivity and Specificity - Boruah, Deb K.; Vishwakarma, Daisy; Gogoi, Pallavi; Lal , Navneet R; Deuri, Arup (Acta medica Lituanica, 2023)
Background: High-resolution Ultrasound (USG) provides good anatomical details of the ocular posterior segment and depicts the various pathological conditions affecting the ocular posterior segment, which helps ophthalmologists for choosing the best treatment options. This study aims to evaluate the utility of High-resolution Ultrasonography in the Evaluation of Posterior Segment Ocular lesions by using Sensitivity and Specificity.Materials and Methods: A hospital-based retrospective study enrolled 81 patients in a tertiary care hospital. Clinical and ophthalmological examinations were performed followed by USG of the orbits. B-mode USG was done with a 7.5–13 MHz linear probe. The final diagnosis was made by correlating the USG findings with clinical and ophthalmological examinations.Statistical analysis: Sensitivity, specificity, the positive predictive value, the negative predictive value, and the accuracy of B-scan USG were compared with the ophthalmological findings by using the Chi-square test.Results: Of 81 patients (n=48 males and n=33 females) with a mean age of 38.98 ± 16.48 [SD] years, posterior segment ocular lesions in association with cataracts were found in 27 (33.3%) patients, whereas 14 (51.9%) patients had posterior vitreous detachment (PVD), 10 (37%) patients had retinal detachment (RD), and 1 (3.7%) patient had choroidal detachment (CD). Posterior segment ocular pathologies were found in 17 (21%) patients with blunt ocular injuries, whereas 8 (47.1%) patients had PVD, 4 (23.5%) patients had RD and 4 (23.5%) patients had CD. The ocular USG had a sensitivity of 87.32%, specificity of 80%, and accuracy of 86.42% with a statistically significant difference between the USG findings and the Ophthalmology diagnosis of the posterior segment ocular abnormalities of a p-value of 0.0005.Conclusion: High-resolution ultrasound is one of the best and an easily available imaging modality for the evaluation of posterior segment ocular pathologies, especially in the presence of opaque ocular media.
Keywords: ultrasonography (USG); posterior segment; posterior vitreous detachment (PVD); retinal detachment (RD); choroidal detachment (CD)